Strategic alignment, process improvements and public value in public-private IT outsourcing in Mexico. Issue 5 (12th February 2021) - Duhamel, Francois; Gutiérrez-Martínez, Isis; Picazo-Vela, Sergio; Luna-Reyes, Luis Felipe
Abstract : Purpose: The authors propose a conceptual model that explains how interorganizational relations in public-private IT outsourcing (ITO) may enhance public value in public administrations through process improvement. Design/methodology/approach: The research design is based on the development of a theoretical framework based on the integration of transaction cost theory (TCT) and the resource-based view (RBV), and empirical interview data from IT managers in state and local governments in Mexico. Findings: First, public-private ITO does produce specific process improvements in Mexico's public administration given its specific institutional context. Second, public value depends on the alignment between the characteristics of IT project activities and the attributes of outsourcing as a mode of governance. Third, process improvements moderate this relation. Fourth, relevant process improvements are identified on an empirical basis, showing the importance of institutional conditions in the determination of public value through interorganizational relationships in the public sector. Practical implications: The authors suggest new roles for public managers as orchestrators of interorganizational relations, and specify the orientation relevant process improvements could take in a specific institutional context. Originality/value: Through this study, it is possible to gain both theoretical and practical understanding of process improvements in public administrations to enhance public value.